Ex vivo toxicological evaluation of experimental anticancer gold(i) complexes with lansoprazole-type ligands. Issue 6 (25th September 2019) - Estrada-Ortiz, Natalia; Lopez-Gonzales, Elena; Woods, Ben; Stürup, Stefan; de Graaf, Inge A. M.; Groothuis, Geny M. M.; Casini, Angela
Graphical Abstract: Abstract: Gold-based compounds are of great interest in the field of medicinal chemistry as novel therapeutic (anticancer) agents due to their peculiar reactivity and mechanisms of action with respect to organic drugs. Despite their promising pharmacological properties, the possible toxic effects of gold compounds need to be carefully evaluated in order to optimize their design and applicability. This study reports on the potential toxicity of three experimental gold-based anticancer compounds featuring lansoprazole ligands (1–3 ) studied in an ex vivo model, using rat precision cut kidney and liver slices (PCKS and PCLS, respectively). The results showed a different toxicity profile for the tested compounds, with the neutral complex 2 being the least toxic, even less toxic than cisplatin, followed by the cationic complex 1 . The dinuclear cationic gold complex 3 was the most toxic in both liver and kidney slices. This result correlated with the metal uptake of the different compounds assessed by ICP-MS, where complex 3 showed the highest accumulation of gold in liver and kidney slices. Interestingly compound 1 showed the highest selectivity towards cancer cells compared to the healthy tissues. Histomorphology evaluation showed a similar pattern for all three Au(i ) complexes, where the distal tubular cells suffered the most extensive damage, in contrast to the damage in the proximal tubules induced by cisplatin. The binding of representative gold compounds with the model ubiquitin was also studied by ESI-MS, showing that after 24 h incubation only 'naked' Au ions were bound to the protein following ligands' loss. The mRNA expression of stress response genes appeared to be similar for both evaluated organs, suggesting oxidative stress as the possible mechanism of toxicity. The obtained results open new perspectives towards the design and testing of bifunctional gold complexes with chemotherapeutic applications.